Social Networks and Colonial Power, a Case Study: The Real Ensign Antonio de la Fuente (1763-1807) - Jerez Brenes, Verónica (2019)
This article proposes the reconstruction of the socioeconomic networks established by Real Ensign Don Antonio de la Fuente through the positions he held in the administrative structure of the Crown and the links he created during his life. As part of the social network system that during the colonial era the elite of Cartago used as a means to strengthen their social bonds via marriage, the economic ones using the bonds and letters of power –both granted and received–, and the prestige that gave him the positions in administrative and justice issues.